Editorial and Critical Reflections on the future of identity moments and social media in China and beyond. Issue 3 (September 2020) - Lim, Tania; Lee, Terence; Zhang, Weiyu
This Special Issue of Global Media and China responds in part to Stuart Hall's famous 1996 invocation, 'Who needs identity?' – to study 'specific enunciative strategies' utilized within 'specific modalities of power' so as to consider identity discourses of the present and of the future. This issue draws upon empirical observations presented and debated at the 2019 Chinese Internet Research Conference held in Singapore in May 2019, as well as theoretical contributions in identity politics and social media, the chosen site or 'modality of power'. This editorial and critical essay reflects upon, complemented and supported by the papers in this issue, the critical and conceptual frameworks that are emerging to critique the global and local complexities, diversity and dynamics resulting from the deeper integration of social media into the everyday lives of Chinese Internet users. It presents an overview of the 2019 Chinese Internet Research Conference proceedings in terms of how social media is used to wrap personal politics into a widening range of identity groupings around gender, class, citizens, pop culture and religion in ways that signal the future of newer forms of identity politics among Internet users in China. Since social media posts and exchanges, while geographically sourced and situated, often transcend their boundaries, the arguments presented here goes beyond China and are global. The shareability of identity mediated by individual, state and public discourses on social and 'anti-social' media during the COVID-19 pandemic within China, Singapore and Australia leads to novel ways of understanding identity politics in globalizing China and strategic uses of Chinese identity.